Evaluating flexibility in small firm financing - Andrey Pavlov; Panikkos Poutziouris; Khaled Soufani (The Journal of Entrepreneurial Finance and Business Ventures, 2004)
The choice of financing source is particularly difficult for a small firm due to the high uncertainty about future liquidity requirements. We show that the techniques of continuous time arbitrage and stochastic control theory may be used not only to value such firms but also to determine the optimal financing policies. In particular, we investigate the choice between liquid, but more expensive, forms of financing and restrictive, but cheaper, sources of capital. In addition to developing an optimal financing policy for a typical firm, we estimate the value of flexibility in a financing arrangement. This, in turn, provides a rational explanation for the otherwise surprisingly high levels of flexible financing used by small firms. Beyond small firm management, our findings have important implications for financial institutions and regulators.
Keywords: 650